Proton and Hydrogen Transport through Hydrogen Environments: Ionization and Stripping - Cariatore, Nelson Daniel (2020)
Data are presented over a wide range of impact energies describing the ionization or stripping probability, projectile energy loss, and ejected electron and recoiling target energies and angles for proton and hydrogen passage through hydrogen astrophysical environments. These kinematic and reaction data are tabulated at three levels of detail for use in heavy-particle (H+, H) and secondary-electron transport simulations: (1) the integral scattering cross section and average values of the distributions of energy and angle of the particles, (2) the singly differential cross sections as a function of particle energy and angle, and (3) a subset of the many possible doubly differential cross sections as functions of the particle energy and angle chosen to be most relevant to transport simulations.